2019
DOI: 10.32598/irj.17.2.149
|View full text |Cite
|
Sign up to set email alerts
|

Impact of SHOFER Computer Game on Visual-Motor Coordination in Children With Hearing Impairments

Abstract: The current study aimed at investigating the impact of SHOFER computer game on visual-motor coordination in children with hearing impairments. Methods: The current pre-test, post-test experimental study was conducted in Ahvaz, Iran in 2018. Sixteen preschool children with hearing impairment were randomly assigned into two groups of experimental (n=8) and control (n=8). The experimental group subjects played the SHOFER computer game (driving/racing genre) two 45-minute sessions per week for a five consecutive w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(9 citation statements)
references
References 17 publications
1
8
0
Order By: Relevance
“…In another intervention program [37] in which 15 children, 7 boys and 8 girls, aged 7-13 years, with visual-motor coordination problems and mental retardation took part in and who practiced on the Nintendo Wii and CoTras, after 12 sessions of 40 minutes once a week, an improvement in the participants' visual perception and fine motor skills was observed. Improvements in the visuomotor perception of deaf preschool children with DCD were also observed in a study [34], conducted in 2018 in Iran (Table 3). The experimental study involved 16 deaf preschool children with DCD, who were divided into two groups: an experimental group of 8 people, of which 5 were boys, average age 7.10 years and a control group of an equal number of children with 4 boys, average age 7.9 years (Tables 2 & 3).…”
Section: Evaluation Of Interventions In Children With Dcd and Co-morb...supporting
confidence: 53%
See 4 more Smart Citations
“…In another intervention program [37] in which 15 children, 7 boys and 8 girls, aged 7-13 years, with visual-motor coordination problems and mental retardation took part in and who practiced on the Nintendo Wii and CoTras, after 12 sessions of 40 minutes once a week, an improvement in the participants' visual perception and fine motor skills was observed. Improvements in the visuomotor perception of deaf preschool children with DCD were also observed in a study [34], conducted in 2018 in Iran (Table 3). The experimental study involved 16 deaf preschool children with DCD, who were divided into two groups: an experimental group of 8 people, of which 5 were boys, average age 7.10 years and a control group of an equal number of children with 4 boys, average age 7.9 years (Tables 2 & 3).…”
Section: Evaluation Of Interventions In Children With Dcd and Co-morb...supporting
confidence: 53%
“…Regarding movement accuracy [47,50], one of the two studies [50] showed an improvement in both the experimental group and the control group, something that was not observed in the study by Jelsma et al [47], where no improvement was found for children in the intervention group. Regarding motor learning [34,52], and motor performance [57,62], it was not found in the examined research papers sufficient evidence to support or refute the use of interactive games to improve the above factors. However, a significant improvement was observed in the predictability of the movements and in the saving of forces during the execution of the activities (Bonney et al, 2017a;Kuijpers et al, 2021).…”
Section: Effectiveness Of Intervention Programsmentioning
confidence: 99%
See 3 more Smart Citations